PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MENGOLAH MAKANAN KONTINENTAL DI SMK NEGERI 3 KOTA KEDIRI - Yesha Yolanda Eka Yustina; Mauren Gita Miranti; Luthfiyah Nurlaela; Andika Kuncoro Widagdo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of students in the Continental Food Processing subject at SMK Negeri 3 Kediri City, characterized by passive attitudes, lack of active participation, and low student engagement caused by the dominant use of a monotonous direct instruction model. This study aims to determine the effect of the Team Games Tournament (TGT) cooperative learning model on student learning outcomes in the basic sauce material. The method used was quasi-experimental with an Equivalent Control Group Design, involving class X Culinary 2 as the experimental group (n=36) and class X Culinary 4 as the control group (n=35), selected through purposive sampling. Data were collected using pre-test and post-test instruments that had been tested for validity and reliability, then analyzed using normality, homogeneity, independent sample t-test, and simple linear regression tests. The results showed an increase in the mean score of the experimental group from 56.11 to 78.61, while the control group increased from 55.71 to 66.29. The independent sample t-test on post-test data produced a significance value of <0.001 (<0.05), leading to the rejection of H0 and the acceptance of Ha. The 12.325-point difference in post-test mean scores proves that the TGT learning model is more effective than the direct instruction model in improving student learning outcomes.